The Choices in Translating Song that Emma Heesters Used when Translating the Lyrics - Muhammad Natsir; Anggraini Thesisia Saragih (Randwick International of Education and Linguistics Science Journal, 2023)
The aims of this study were to investigate the techniques translating choices found in translated covered lyrics of “Melukis Senja”, “Maafkan Aku”, and “Cuek” by Emma Heesters. The study was conducted by using a content analysis research. The data of this study were taken from the lyrics of “Melukis Senja”, “Maafkan Aku”, and “Cuek”. The data of this study were the translated lyrics songs that appeared in “Melukis Senja”, “Maafkan Aku”, and “Cuek” songs. The data analysis was taken by observing, take notes, make a table the data based on the theory proposed by Franzon and Low. There are four kinds of translating choices techniques found in Emma Heesters covered lyrics. The result of analysis for each kind of translation choices were: Leaving the song untranslated, there were 1, Writing new lyrics but not taking the music into account, there were 8, Translating the lyrics and adapting the music accordingly, there were 26, and Adapting the translation to the original music, there were 22.